Distribution and genetic diversity among Aspergillus flavus isolates across three agro-ecologies essential for maize cultivation in Ghana - Dadzie, M.A.; Oppong, A.; Ofori, K.; Eleblu, J.S.Y.; Ifie, B.E.; Blay, E.T.; Obeng-Bio, E.; Appiah-Kubi, Z.; Warburton, M.L. (Plant Pathology, 2019)
Fungal mycotoxins are important contaminants of agricultural commodities that pose serious concerns to producers, consumers and exporters. Aflatoxin is a carcinogenic metabolite produced by the fungi Aspergillus flavus and A. parasiticus. These fungi and other mould species living in the soil contaminate several crops including maize. This study was undertaken with the following objectives: (i) to assess the presence of A. flavus and other moulds in Ghanaian soil; (ii) to determine the distribution and density of A. flavus under three agro-ecologies noted for major maize production; and (iii) to assess the effect of percentage of carbon (C) and nitrogen (N) and soil pH on A. flavus population densities and diversity in the isolates found across the agro-ecologies. The data showed seven moulds that were common across the agro-ecologies. Significant differences (P < 0.05) were observed in the A. flavus density and distribution within and across these agro-ecologies. Fumesua soils recorded the highest levels of A. flavus (1.185 9 103 cfu g 1) while Akomadan recorded the least (9.76 9 102 cfu g 1). Percentage available C, N and soil pH did not significantly influence A. flavus density. The A. flavus isolates identified in this study varied in genetic sequence within the aflatoxin gene cluster, but these differences were not distinguishable by origin
Research Article
Keywords: aflatoxin; Aspergillus flavus; contamination; diversity